The Study of Business Actors Readiness for the Obligation to Implement Halal Certification in West Nusa Tenggara - Dyah Pikanthi Diwanti (Jurnal Ilmiah Ekonomi Islam, 2023)
The objective of the study is determining the readiness of business actors, in this case, micro, and small business actors in West Nusa Tenggara (Nusa Tenggara Barat – NTB). The challenge faced by the consumers is the limited products that have been certified halal. There are still many services or products that are a necessity for most consumers which are not yet halal-certified. This is what makes consumers immaterially disadvantaged, namely: consumers do not get their rights to obtain halal services or products. Therefore, the government and stakeholders need to provide guidance to business actors and consumers. On the other hand, a small number of MSME business actors still consider halal certification to be a hassle, so they are reluctant to be certified as halal. Another factor that hinders the implementation of halal product guarantees is that information about products from business actors is still not disclosed. The research is conducted with descriptive qualitative method. The research informants are micro and macro entrepreneurs in NTB. The data collection techniques use questionnaires or questionnaires, interviews, and documentation to get more in-depth results and avoid bias. The data analysis uses the Miles and Huberman model which consists of four activities of data collection, data reduction, data display, and conclusion/verification. The results obtained from the implementation of halal certification are not optimal. There are still many MSME actors who are not aware of the importance of halal certification in the processed food products they produce.